2017
DOI: 10.1038/srep39785
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recall Ability of Memory T cells is Encoded in their Epigenome

Abstract: Even though T-cell receptor (TCR) stimulation together with co-stimulation is sufficient for the activation of both naïve and memory T cells, the memory cells are capable of producing lineage specific cytokines much more rapidly than the naïve cells. The mechanisms behind this rapid recall response of the memory cells are still not completely understood. Here, we performed epigenetic profiling of human resting naïve, central and effector memory T cells using ChIP-Seq and found that unlike the naïve cells, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 55 publications
6
33
0
Order By: Relevance
“…A genome-wide analysis of histone modifications (H3K4me1, H3K4me3, and H3K27ac) in human naive, central memory, and effector memory CD4+ T cells revealed that loci coding for various cytokines including IFNg, IL4, IL13, IL17, and IL22 are enriched in activating histone marks as compared to naive cells. In addition, they are more rapidly induced in memory than in naive T cells upon stimulation (Barski et al, 2017;Durek et al, 2016). Similar patterns were observed at gene loci coding for T-bet and RORC transcription factors known to be important regulators for effector molecules induced in memory CD4 + T cells upon stimulation that, for instance, drive IFNg and IL17 expression, respectively.…”
Section: Cell Host and Microbesupporting
confidence: 58%
See 1 more Smart Citation
“…A genome-wide analysis of histone modifications (H3K4me1, H3K4me3, and H3K27ac) in human naive, central memory, and effector memory CD4+ T cells revealed that loci coding for various cytokines including IFNg, IL4, IL13, IL17, and IL22 are enriched in activating histone marks as compared to naive cells. In addition, they are more rapidly induced in memory than in naive T cells upon stimulation (Barski et al, 2017;Durek et al, 2016). Similar patterns were observed at gene loci coding for T-bet and RORC transcription factors known to be important regulators for effector molecules induced in memory CD4 + T cells upon stimulation that, for instance, drive IFNg and IL17 expression, respectively.…”
Section: Cell Host and Microbesupporting
confidence: 58%
“…Similar patterns were observed at gene loci coding for T-bet and RORC transcription factors known to be important regulators for effector molecules induced in memory CD4 + T cells upon stimulation that, for instance, drive IFNg and IL17 expression, respectively. Furthermore, there is a positive correlation between gain of H3K4me3 in memory CD4+ T cells at gene loci that are more inducible in memory cells than naive T cells, suggesting their poised status in memory cells (Barski et al, 2017).…”
Section: Cell Host and Microbementioning
confidence: 99%
“…Of the genes that exhibited larger H3K4me3 peaks in the control group, 22 (91.6%) were downregulated and 2 (8.4%) were upregulated (Figure 3A). This pattern of directional gene expression correlating with H3K4me3 for the control and infected samples is consistent with the literature (Barski et al, 2017; Clouaire et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have shown that increased H3K4me3 is frequently accompanied by an increase in PolII occupancy and elevated expression of proximal genes (Barski et al, 2017; Clouaire et al, 2012). In the present study, we observed that H3K4me3 is accompanied by an increase in PolII occupancy (Figure 1 and supplementary figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the expression levels of CD28 might have an impact in the immune response initiated, as influenza infected mice treated with CTLA4Ig shift their memory T cell pool to one 450 predominantly composed of central memory cells, while influenza specific memory cells in untreated mice were predominantly effector cells (Ndejembi et al, 2006). This could explain why activated effector memory T cells produce cytokines more efficiently than central memory T cells (Barski et al, 2017). Finally, the variability in expression of the CD28 receptor between young and old is only significant in effector memory T cells (Koch et al, 455 2008).…”
Section: Discussionmentioning
confidence: 99%